Effects of Model Development for Preventing Early Postpartum Hemorrhage Combined with Lower Uterine Segment Compression and Cold Massage in Mothers Receiving Labor Services Rangae Hospital, Narathiwat Province - Buahom, Kanjana; Nawakaning, Rorbia; Salae, Hudaibah; Chantasiro, Warintorn; Hayeese, Wanisa (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Postpartum hemorrhage is a major cause of maternal death. Health Service Area 12 had the highest maternal mortality rate at 72.6 % (Ministry of Public Health, 2022). Rangae Hospital has seen a rise in postpartum hemorrhage in the first two hours from 2021 to 2023, with rates of 0.37 %, 0.4 %, and 0.97%, respectively. The most common causes were uterine atony and retained placenta. To develop a model for preventing early postpartum hemorrhage and compare the total blood loss between the experimental group using the developed model and the control group receiving standard care. Methods The research and development model consisted of 4 steps: 1) Problem and needs analysis (R1): Data providers were mothers with a history of postpartum hemorrhage and professional nurses working in the labor room; 2) Model design and development (D1): Researchers drafted the model and had experts review its quality; 3) Model testing and effectiveness evaluation (R2): The study population consisted of women giving birth at Rangae Hospital. The sample consisted of 50 women who delivered normally, divided into 25 in the experimental group and 25 in the control group. The tools used were the early postpartum hemorrhage prevention model, the lower uterine segment compression model, and the cold massage model, including a personal information questionnaire and a record of blood loss volume within 2 hours postpartum. Data were analyzed using descriptive statistics (t-test); 4) Evaluation of the developed model (D2): Data providers were 25 women who used the developed model. Results The early postpartum hemorrhage prevention model included professional standard labor care combined with lower uterine segment compression and uterine massage for 10 minutes, as well as uterine massage with cold compresses. The amount of blood loss in the first 2 hours after delivery in the experimental group using the postpartum hemorrhage prevention model was 119.60 milliliters on average (S.D. = 18.82). The control group receiving standard care had an average of 206 milliliters (S.D. = 36.74). The amount of blood loss in the experimental group was significantly statistically less than in the control group (t = 10.46, p < 0.000). Conclusion and Recommendation The study results show that the early postpartum hemorrhage prevention model combined with lower uterine segment compression and cold massage effectively reduces postpartum hemorrhage. This provides guidance for nurses in caring for mothers receiving labor services, leading to rapid diagnosis and treatment and ensuring safe delivery.